Genomics Of Banana Streak Viruses And Development Of Specific Immunodiagnostics For Routine Indexing (Journal of Plant Disease Sciences, 2020)
A cryptic Badnavirus species complex, known as banana streak viruses (BSV) poses a serious threat to banana production and genetic improvement worldwide. Present study reports full genome sequences of episomal banana streak MY virus (BSMYV) and banana streak OL virus (BSOLV) variants using improved rolling circle based amplification. The recombination analysis revealed the existence of extensive recombination within the banana streak viruses and sugarcane bacilliform viruses (intra-BSV and intra-SCBV recombination events). A total of 32 unique recombination events within banana and sugarcane badnaviruses (inter BSV-SCBV) were detected. The putative coat protein (CP) coding region (p37) of BSMYV was identified, in vitro expressed and used as antigen for raising polyclonal antiserum. The anti p37 antiserum was successfully used in antigen coated plate-enzyme linked immunosorbent assay (ACP-ELISA). By employing the developed antibodies, ACP-ELISA, double antibody sandwich-ELISA (DAS-ELISA) and a sensitive duplex-immunocapture-PCR (D-IC-PCR) was standardized for the sensitive, reliable and accurate routine indexing of episomal BSV.
Keywords: Banana streak viruses; Integrants; Immunodiagnostics; Indexing